PENGARUH GROSS DOMESTIC PRODUCT (GDP) DAN NILAI TUKAR NEGARA MITRA DAGANG TERHADAP EKSPOR UDANG INDONESIA TAHUN 2009-2015 - Wisnu Sujatmiko; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2019)
International trade is one of the economic activities that an important role for a country. The benefits of international trade are related to economic growth, national development and national welfare. The limited condition of resources is no longer a barrier to fulfilling the needs of a country with exchange and trade. Shrimp is one of the leading export commodities for Indonesian fishery products. The value of shrimp exports is the highest of the other main fishery commodities. Export demand is influenced by Gross Domestic Product and exchange rates. The purpose of this study is determine the effect of Gross Domestic Product and exchange rate of trading partner countries on Indonesian shrimp exports. The type of data used is the state panel data of Indonesian shrimp export partners in 2009-2015. The method used is panel data regression. The results show that Indonesian shrimp exports with Gross Domestic Product are positive and significant. While the exchange rate has a negative and significant effect on Indonesian shrimp exports.